UJI ISOLAT BAKTERI SELULOLITIK SEBAGAI DEKOMPOSER PADA DEKOMPOSISI TANDAN KOSONG KELAPA SAWIT - Clara Aprilya Kurniawan; Gusmawartati Gusmawartati (Percetakan Umi Toaha Makassar, 2021)
Oil palm empty fruit bunches (OPEFB) is one of the largest types of solid waste produced by palm oil mills (POM). Each processing of 1 ton of fresh fruit bunches (FFB) produces 220–230 kg of empty fruit bunches (EFB). One of the attempts to overcome the accumulation of EFB is by composting. The main obstacle in composting OPEFB is the process of overhauling, it takes 6-12 months because OPEFB contains 33.02% cellulose, 22.05% hemicellulose and 35.08% lignin. One of the efforts to speed up the composting is using biological treatment by adding microorganisms such as cellulolytic bacteria which are capable in producing cellulase enzymes. The reseach was carried out experimentally using a non-factorial completely randomized design (CRD) consisting of eight treatments, namely B0 (control), B (Bacillus tequilensis Strain RA 1402), B2 (Bacillus subtilis Strain C17), B3 (Bacillus subtilis Strain SKUASIS) , B4 (Bacillus subtilis Strain DSM 10), B5 (Bacillus subtilis Strain K43), B6 (Pseudomonas aeruginosa Strain KUJM) and B7 (Combined Isolates). The parameters observed were physical properties of compost, weight loss of compost and total of compost microb population. The resultof the research showed that cellulolytic bacteria isolates had a significant effect on weight loss of compost, pH. The combined isolates (B7) is the best treatment in increasing compost material weight, pH. The treatment B7 has the best ability in producing high quality compost which is under the SNI Compost Quality Standard: 19−7030−2004.